CCA2 Attack and Modification of Huang et al .’s Public Key Encryption with Authorized Equality Test - Lee, Hyung Tae (2017)
In this article, we identify a flaw in Huang et al.'s public key encryption with authorized equality test (The Computer Journal, 2015). More precisely, we point out that the proof of the indistinguishability under adaptive chosen ciphertext attack (IND-CCA2) security for their scheme has a serious flaw. We illustrate this flaw by presenting a polynomial time CCA2 attack on their scheme. We also provide a solution to correct this flaw by modifying their scheme slightly. Our solution is quite efficient because it provides security against CCA2 attack by exploiting only the hash computation of a two times longer input without any increase in the sizes of ciphertexts and warrants.